Suicide risk among adult subjects hospitalized in an acute psychiatric ward: 6-year retrospective investigation - Di Lorenzo, Rosaria; Scala, Carmela; Reami, Matteo; Rovesti, Sergio; Ferri, Paola (BMC public health, 2024)
Background The phenomenon of suicide risk (SR) represents a psychiatric, social and environmental emergency. The acute psychiatric ward as the Italian Service for Psychiatric Diagnosis and Care (SPDC) represents the place where SR is high due to the acute and serious conditions of people hospitalized. The objective of this study was to evaluate the characteristics of subjects admitted to a SPDC over a 6-year period for SR represented by: suicidal ideation, attempted and failed suicide. Methods With a retrospective single-center observational design, we collected hospitalizations from 01/01/2017 to 31/12/2022 in the SPDC of AUSL-Modena for SR, analyzed the modality of SR and compared the demographic and clinical variables of subjects with SR with those hospitalized for other clinical reasons in the same period. Data were statistically analyzed. Results In the 6-year of study period, we collected 2,930 hospitalizations in the SPDC of AUSL- Modena and among them, 68% ( n = 528) were carried out due to SR, which represented the second leading cause of hospitalization (18%), in particular among females (Pearson Chi2 = 17.41, p < 0.001). Individuals with SR were more frequently voluntary admitted (Pearson Chi2 = 215.41, p < 0.001) for a shorter period (7.36 ± 8.16 vs 11.66 ± 15.93, t = 6.03, t-test, p < 0.001) and less frequently repeated the hospitalization during the study period for the same reason (Pearson Chi2 = 6.0, p = 0.014). The most frequent psychiatric disorders associated with SR were depressive, personality and adjustment disorders, which represented the most common factor associated with SR (68%), followed by family/relationship problems (12%) and alcohol/substance abuse (8%). We highlighted three kinds of suicidal risk: suicidal ideation (40%), often associated with personality disorders and substance use disorders, drug ingestion (30%) concomitant with conflicting family relationships and use of violent means (30%) associated with depressive disorders (Pearson Chi2 = 42.83, p = 0.002). Conclusions Our study provides a real-world setting evaluation of subjects hospitalized for SR and, in accordance with literature, suggests that suicidal behavior is the product of many clinical and social factors’ interaction, that occurred in a crucial moment of life in vulnerable individuals. The identification of subjects at SR represents the first step of preventive multi-professional interventions.